Footloose and fancy-free in FinTech? Internationalization strategies of born regional and born global firms in the European financial service sector - Paulina Forsberg; Willem Hulsink (Journal of International Entrepreneurship, 2024)
Due to economic globalization and technological advancements, businesses are increasingly required to navigate complex international markets. One type of firm that has emerged in response to these trends is the born global, which initiates foreign activities almost from the very start. While these startups expand their reach by pursuing pro-active internationalization strategies, it is unclear whether startups creating the FinTech revolution also belong to this category. This study investigates five key components of the internationalization strategies of European FinTech startups: the speed and scope of internationalization, the drivers of internationalization, international market selection, the mode of market entry, and the challenges involved in internationalization. While born globals use a systematic approach to international market selection and entry, European FinTechs use a quasi-systematic and opportunistic approach to searching and seizing their geographical markets. Their common approach includes quickly going beyond their home base to adjacent markets, followed by gradual experimentation and substantive growth in their home region, and becoming born-regional firms (with some evolving into born-global firms later).
Keywords: 330; Born global firms; Born regional firms; Country selection; Entry; Europe; Fintech startups; Financial services; Internationalization; Strategies